The Analysis of User Satisfaction of SMAIT Raudhatul Jannah Cilegon Website Using PIECES Method - Safrina, Adhelia Permata; Karyati, Cut Maisyarah (PT Mattawang Mediatama Solution, 2025)
Technological advancement in the education sector has transformed how institutions communicate and deliver services, particularly through digital platforms such as websites. SMAIT Raudhatul Jannah Cilegon developed its official website to facilitate access to information for teachers, students, and prospective students. However, user satisfaction remains a crucial benchmark for evaluating the effectiveness and quality of such platforms. This study aims to analyze the level of user satisfaction with the SMAIT Raudhatul Jannah website using the PIECES method, which includes six dimensions: Performance, Information, Economy, Control (Security), Efficiency, and Service. The research employs a quantitative approach with 100 respondents, using a questionnaire distributed via Google Form. The data were analyzed through validity and reliability testing, Likert scale assessment, and descriptive statistics using SPSS. The results indicate that overall user satisfaction falls into the